The Development of Innovative Banana with Monggo Smoothie: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Today’s hot and sunny season shows that different methods are used to cool the summer breeze. One way to do this is to drink a soothing drink. In the Philippines, where the summer season can reach 32 degrees Celsius, many Filipinos have different skills to deal with this hot season. For example, shakes and smoothies with many exotic fruits and vegetables in the Philippines match with many possible mixtures or vegetables of fruits. It is also extraordinary news that promotes the health benefits of a given fruit—specific information, process, and data requirements. The promotes used both descriptive method and experimental to help proponents optimize the smoothie's innovation for enhancing the flavour and the nutrition that will provide for the respondents. The proponent used a series of surveys and questionnaires to determine the quality of product development and the product's nutritional value. The following were the prominent findings of this research based on the gathered data: on the demographic profile of 50 respondents: as to gender, 25% or 50% are female; 20% or 40% of the respondents are from ages 18 and below.Regarding the benefits, 25% or 50% tasting the smoothie sample responded satisfactorily. Regarding the presentation, 29% or 58%, tasted the smoothie sample and responded with good satisfaction. As to the presentation, 20% or 40% gives average satisfaction. Choosing the right ingredients to make a healthy banana with munggo smoothie: fruit shake well balance of its sweetness and nutrition. All the ingredients needed to make a banana with munggo smoothie are Sugar, Condensed milk, Banana, Munggo, [Munggo Beans], and Fresh milk.
Keywords: Development; Banana with Monggo; Taste